Alcaloides isoquinolínicos isolados das partes aéreas de Worsleya procera (Lem.) Traub (Amaryllidaceae) - Moraes, Carolina Torres (2016)
Many natural compounds have shown interesting biological and pharmacological activities and are considered important targets and one of the largest sources of new drugs, used directly or indirectly as a starting point for developing new drugs. Of plant compounds with biological potency, the alkaloids present in the Amaryllidaceae family are especially effective, for example, the alkaloid galanthamine, a selective, reversible and competitive inhibitor of the enzyme acetylcholinesterase and is marketed for the treatment of Alzheimer's disease. No study of chemical and biological characterization of the plant Worsleya procera(Lem.)Traub (Amaryllidaceae) was found in the literature and thus, for the purpose of phytochemical characterization of this plant, various chromatographic techniques were used in their extracts for the isolation and identification of alkaloids. As a result, 19 alkaloids and a mixture of two epimers alkaloids (18and 19)were isolatedfrom the aerial parts of W. procera: 3-epimacronine (1),albomaculine (2), lycorine (3), galanthine (4), tazettine (5), hippeastrine (6), O-methyllycorenine (7), 7-methoxy-O-methyllycorenina (8), homolycorine (9), 8-O-demethylhomolycorine (10), trisphaeridine (11), haemanthamine (12), 8-O-demethyl-O-methyllycorenine (13), ismine (14), 6-O-methylpretazettine (15), pretazettine (16), alkaloidwith skeleton type haemanthamine(17), haemanthidine (18), 6-epihaemanthidine (19), 8-O-demethyl-2a-hydroxyhomolycorine (20) e N-fomylismine (21), where their structures could be elucidated by the 1H NMR technique one-and two-dimensional, in compared with literature data. The alkaloid 8-O-demethyl-2a-hydroxyhomolycorineis reported for the first time from natural source.Nineisolated alkaloids(Tazettine, 3-epimacronine, albomaculine, lycorine, galanthine,hippeastrine, O-methyllycorenine, 7-methoxy-O-methyllycorenina and 8-O-demethylhomolycorine) were evaluated for antimicrobial activity, with all weak activity when compared to posivito control.The GC-MS technique proved to be a rapid and efficient technical alkaloids identification, since the analysis results of W.proceraplantextractsfound that the majority were alkaloids 22with skeleton homolicorina type, skeleton lycorinetype and skeletontazetina type, which was confirmed by the total mass of alkaloid obtained